Double somatic mutations in CTNNB1 and GNA11 in an aldosterone-producing adenoma - Nanba, Kazutaka; Blinder, Amy R.; Udager, Aaron M.; Hirokawa, Yuusuke; Miura, Takayoshi; Okuno, Hiroshi; Moriyoshi, Koki; Yamazaki, Yuto; Sasano, Hironobu; Yasoda, Akihiro; Satoh-Asahara, Noriko; Rainey, William E.; et al. (Frontiers in Endocrinology, 2024)
Double somatic mutations in CTNNB1 and GNA11/Q have recently been identified in a small subset of aldosterone-producing adenomas (APAs). As a possible pathogenesis of APA due to these mutations, an association with pregnancy, menopause, or puberty has been proposed. However, because of its rarity, characteristics of APA with these mutations have not been well characterized. A 46-year-old Japanese woman presented with hypertension and hypokalemia. She had two pregnancies in the past but had no history of pregnancy-induced hypertension. She had regular menstrual cycle at presentation and was diagnosed as having primary aldosteronism after endocrinologic examinations. Computed tomography revealed a 2 cm right adrenal mass. Adrenal venous sampling demonstrated excess aldosterone production from the right adrenal gland. She underwent right laparoscopic adrenalectomy. The resected right adrenal tumor was histologically diagnosed as adrenocortical adenoma and subsequent immunohistochemistry (IHC) revealed diffuse immunoreactivity of aldosterone synthase (CYP11B2) and visinin like 1, a marker of the zona glomerulosa (ZG), whereas 11β-hydroxylase, a steroidogenic enzyme for cortisol biosynthesis, was mostly negative. CYP11B2 IHC-guided targeted next-generation sequencing identified somatic CTNNB1 (p.D32Y) and GNA11 (p.Q209H) mutations. Immunofluorescence staining of the tumor also revealed the presence of activated β-catenin, consistent with features of the normal ZG. The expression patterns of steroidogenic enzymes and related proteins indicated ZG features of the tumor cells. PA was clinically and biochemically cured after surgery. In conclusion, our study indicated that CTNNB1 and GNA11-mutated APA has characteristics of the ZG. The disease could occur in adults with no clear association with pregnancy or menopause.